NEUROPROTECTIVE EFFECTS AND MECHANISM OF CMS121 IN A NEURON MODEL OF OXYGEN-GLUCOSE DEPRIVATION/REPERFUSION AND A MOUSE MODEL OF ISCHEMIA-REPERFUSION - ZHAO Zhiyuan, ZHAO Rui, LIU Wenhao, SUN Chengjian, XU Rui (精准医学杂志, 2023)
Objective To investigate the neuroprotective effects and mechanism of CMS121 in a neuron model of oxygen-glucose deprivation/reperfusion (OGD/R) and a mouse model of ischemia/reperfusion (I/R). Methods Cortical neurons were divided into control group (normal culture), OGD/R group (OGD/R model construction), and OGD/R+CMS121 group (OGD/R model construction plus treatment with CMS121). All neurons’ viability and lactate dehydrogenase (LDH) release were assessed after 24 h of reperfusion. Western blotting was performed to measure the expression of protein kinase B (Akt) and phosphorylated Akt (p-Akt) in the neurons after 6 and 24 h of reperfusion. C57BL/6J mice were randomly divided into sham group (sham operation), I/R group (I/R model construction), and I/R+CMS121 group (I/R model construction plus treatment with CMS121). After 24 h of reperfusion, we assessed the neurological damage of the mice with the Neurological Severity Score (NSS), and calculated the brain infarct volume (as a percent of total brain volume) after 2,3,5-triphenyltetrazolium chloride staining. Results There were significant differences in cell viability and LDH release between the three neuron groups (F=71.21,88.93,P<0.01). Compared with the OGD/R group, the OGD/R+CMS121 group showed significantly increased neuronal viability and significantly reduced LDH release (t=5.56,11.63,P<0.05). Time, group, and time × group interaction significantly affected neuronal p-Akt expression (F=13.48-32.67,P<0.01), and showed no significant effects on Akt expression (P>0.05). After 6 h reperfusion, a significant difference was observed in neuronal p-Akt expression between the three neuron groups (F=18.78,P<0.01). Neuronal p-Akt expression was significantly increased in the OGD/R and OGD/R+CMS121 groups than in the control group (P<0.01), and showed no significant difference between the OGD/R and OGD/R+CMS121 groups (P>0.05). After 24 h reperfusion, p-Akt expression differed significantly between the three neuron groups (F=38.50,P<0.01). The expression of p-Akt was significantly increased in the OGD/R+CMS121 group than in the control and OGD/R groups (P<0.01), and showed no significant difference between the OGD/R and control groups (P>0.05). There were significant differences in the NSS score and infarct volume between the three mouse groups (F=20.24,118.60,P<0.01). Compared with the I/R group, the I/R+CMS121 group had a significantly decreased NSS score and a significantly reduced infarct volume (P<0.05). Conclusion CMS121 has neuroprotective effects in the neuronal OGD/R model and mouse I/R model, possibly through upregulating Akt phosphorylation in cortical neurons.